Neuropsychological and Neuroimaging Outcomes Following Moderate to Severe Paediatric Traumatic Brain Injury in South Africa - Mc Fie-Schwartz, Sarah (Department of Psychology, 2023)
Paediatric traumatic brain injury (pTBI) is a leading cause of mortality and disability. South Africa is predicted to have a high pTBI rate and an adverse socioeconomic environment for recovery. Despite this, few studies have investigated the neuropsychological and/or neuroimaging outcomes of pTBI in South Africa. The study was designed as a capacity-building exercise to demonstrate the successful collection of data from different sites involved in a developing international collaboration. The aims were therefore to 1) provide a detailed description of the premorbid factors and neuropsychological and neuroimaging outcomes of a sample of South African children with moderate to severe pTBI, and 2) investigate the barriers to the successful implementation of neuropsychological and neuroimaging research in this population. Five patients with severe pTBI were enrolled during the 6-month recruitment window. These participants presented with 6-month post-TBI outcomes that ranged from mild neuropsychological deficits and no visible abnormalities on neuroimaging to severe neuropsychological deficits and evidence of multifocal pathology on imaging. There was a relatively high occurrence of adverse developmental, socioeconomic, and neuropsychological histories, which will need to be considered when selecting an appropriate control group or combining with other populations in a potential future multicentre study. Additional strategies will also be required to improve recruitment and increase the rate of successful imaging. Changes may need to be made to the neuropsychology assessment so as not to disadvantage this population, for example avoiding tests that are reliant on sequencing the alphabet. In conclusion, the study's findings will help to improve the likelihood of the much-needed large-scale research in this at-risk and understudied South African population.